ESTIMATION OF AGRICULTURE SAVE GARUT CHIPS WITH ACCELERATED TEST METHOD - Ichda Chayati (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2004)
ion of shelf life 0/ arrowroot chips by accelerated test was 'I1Ialea, Arrowroot chips from KKPA was fried, packed, and kept at and -IO